A Nationwide Analysis of Preoperative Planning on Operative Times and Postoperative Complications in Total Knee Arthroplasty - Sodhi, Nipun; Anis, Hiba K.; Coste, Marine; Ehiorobo, Joseph O.; Chee, Alexander; Freund, Benjamin; Sultan, Assem A.; Moskal, Joseph T.; Scuderi, Giles R.; Mont, Michael A. (The Journal of Knee Surgery, 2019)
Compared with nonelective total knee arthroplasties (TKAs), elective procedures have more time for preoperative planning, which allows for potentially improved patient optimization, risk factor modification, and patient education. The purpose of this study was to (1) determine nationwide trends in operative times and (2) evaluate associations between surgery type, elective or nonelective, with respect to (a) operative times, (b) length of stay (LOS), (c) discharge dispositions, (d) 30-day postoperative complications, (e) reoperations, and (f) readmissions. The American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database was queried for all primary TKAs performed between 2011 and 2016. This yielded 209,178 cases which were stratified into elective and nonelective cases. Elective cases were those in which patients were brought from their normal living environment for scheduled procedures. One-way ANOVA (analysis of variance) was used to evaluate associations between operative times and year of surgery. Multivariate linear and logistic regression models adjusted for surgery year and patient factors (age, sex, BMI [body mass index], and ASA [American Society of Anesthesiologists] score) were used to evaluate associations of surgery type with peri- and postoperative outcomes. A significant inverse correlation between operative times and operative year was observed (p < 0.001). Mean operative times and LOS were significantly shorter in elective cases compared with nonelective cases (93 vs. 112 minutes, p < 0.005; 3 vs. 5 days, p < 0.001). Multivariate analysis showed these associations remained significant even after adjusting for potential confounders (p < 0.001). Compared with the nonelective cohort, patients in the elective cohort were more likely to be discharged home (74 vs. 69%, p < 0.001). Nonelective patients had higher rates of pneumonia (0.7 vs. 0.3%, p = 0.005), organ-space surgical site infections (SSI; 0.4 vs. 0.2%, p = 0.004), transfusions (10.9 vs. 6.5%, p < 0.001), sepsis (0.6 vs. 0.2%, p = 0.001), and septic shock (0.2 vs. 0.1%, p = 0.005) compared with elective patients. These associations remained significant with multivariate logistic regression. This study demonstrated that preoperative planning can help shorten operative times and LOS as well as reduce complication and reoperation rates. Alongside the direct advantages identified in this study, potential greater effects include superior patient outcomes and reduced health care costs.
Keywords: preoperative planning; elective; nonelective; TKA; outcomes